Efek Spermatogenesis Dan Aprodisiaka Herba Purwoceng (Pimpinella alpina K. D. S.) Pasar Terhadap Tikus Putih Jantan Galur Wistar - Suhartinah Suhartinah (Jurnal Farmasi Indonesia, 2011)
Purwoceng is one of the plants that used traditionally by people in Dieng mountains as aphrodisiac. The use of purwoceng as an aphrodisiac now been extended to other areas and traditional market, usually known as mountain purwoceng, and the part used are the root. The price of purwoceng Dieng is relatively high, while the market purwoceng is relatively affordable. The aim of the experiment was to know the spermatogenesis and aphrodisiac effect of purwoceng herbs infuse from market in Surakarta. Spermatogenesis and aphrodisiac activity test was done using 15 male white mice Wistar strain divided in 3 groups and each group consists of 5 mice. Group I was negative control (water), group II was positive control (purwoceng powder + pasak bumi), group III was purwoceng herbs infuse from market in Surakarta. They were given orally to the mice for 5 days, observed every 2 days. Test of sperm quality was observed on days 0, 2, 4 and 6 which include the number, motility and morphology of spermatozoa. On the 6 th day do weights the testes and seminal vesicles. The aphrodisiac effect was observed behavior of the male white mice by counting the climbing frequency (the male mice climbing on the female mice). The experiment result showed that Purwoceng herb market infuse had an effect on spermatogenesis of male rats and the aphrodisiac on male white mouse wistar strain.